Penerapan Overall Equipment Effectiveness (Oee) Dalam Implementasi Total Productive Maintenance (TPM) (Studi Kasus di Pabrik Gula PT. â€œYâ€.) - Rahmad, Rahmad; Pratikto, Pratikto; Wahyudi, Slamet (Jurnal Rekayasa Mesin, 2012)
In agro-industrial sector especially in sugar factory called PT. â€œYâ€, improvement of manufacturing system is one of an improvement effort that intensively conducted so that later it could responds rapidly to market changes. The company always attempt to improve productivity, one of the way that has been done is implement preventive and corrective maintenance. But in fact, the outcome hasnâ€™t reached the expectation yet. This research found that allocated time to do breakdown maintenance is the main problem, so that most of the corrective action focused in this problem. This research used OEE measurement, Six Big Losses calculation analysis, and also cause-effect diagram to look for existing problem and to give proposed improvement for the problem. As the result, the biggest factors affecting the low effectiveness of machine is reduced speed and breakdown loss so that the proposed improvement action is implementing TPM.Keywords: Preventive Maintenance, Overall Equipment Effectiveness (OEE), Autonomous Maintenance, Total Productive Maintenance (TPM).